Stability study of Fluconazole capsules with Bracketing Design - Aleksandra Chakarjanevska¹; Marika Bogoevska Nikolovska; Mirsada Dervisevic Andonova; Irena Slaveska Spirevska; Marija Karapandzova; Suzana Trajkovic Jolevska; Jasmina Tonic Ribarska (Makedonsko Farmacevtski Bilten)
International Council for Harmonization of Technical Requirements for Pharmaceuticals for Human Use (ICH) guidelines provide guidance for stability monitoring of medicines which Food and Drug Administration (FDA) and European Medicines Agency (EMA) refer to. A full stability study design is described as a model in which samples under the influence of appropriate factors are tested at all-time points. Bracketing and matrixing stability study designs represent reduced designs that may be a suitable alternative to a full stability design. Bracketing design refers to the stability such that only samples on the extremes of certain design are tested at all-time points as in a full design, whereas the stability of the intermediate levels is represented by the stability of the tested extremes, which reduces costs and time analysis. The design assumes that the stability of any intermediate levels is represented by the stability of the extremes tested. Bracketing design of four different dosage strengths of Fluconazole hard capsules is included in this research. The extreme strengths were chosen and parameters average mass of capsule contents, disintegration, dissolution, assay of active and related substances, according to shelf-life specification were tested in accelerated and long-term stability conditions. Based on the obtained results, the stability of any intermediate levels is confirmed by the stability of the tested extremes and show that this reduced design is suitable.